Methodology for Creating a Highway Management Index System - Preety,; Tuteja, Amit (International Journal of Psychosocial Rehabilitation, 2021)
The development of China's roadway system is practically complete, and street maintenance is becoming increasingly important these days. A fundamental test for the majority of the street, the board office is a logical and suitably appropriate procedure for the executives of the highway assistance. A logical administration requires a method for constructing a file arrangement to support the board. In light of the Shenzhen city construction project of a list framework for highway upkeep the board, the author of this paper proposes a method for constructing a file framework for highway upkeep the executives by presenting the executives' idea by objective, as well as incorporating key execution records into the file determination, and finally developing the file arrangement for highway upkeep the executives from five perspectives: security, quality, progress, cost, and condition assurance. By refining and selecting the record among the underlying results of determination using the rule of explicit, measurable, doable, substantial, and time-based, the essayist completes the file arrangement of highway upkeep executives that is appealing to the client.